(untitled) (Research, Society and Development, 2022)
Emergency situations require immediate actions, and the military policeman, when providing first aid to victims, should rely on his knowledge and be aware of his limitations, thus avoiding greater damage and minimizing sequelae. In this context, the elaboration of this article had the objective of performing an integrative literature review in LILACS, SciELO and MEDLINE (BVS) regarding the importance of first aid knowledge for the military policeman. Complete articles published between 2014 and 2020 in Portuguese, English and Spanish were included. Articles published outside the chosen period that did not address the theme of the study, dissertations and theses, and duplicates were excluded. Of the 7,847 articles researched, 6,388 (69.78%) were related to public security, of which 1,321 (14.44%) approached the theme concerning violence and criminality, 1,307 (14.28%) were related to police training, 133 (1.45%) dealt with the theme first aid, and only 5 (0.05%) approached the research’s guiding question. This study demonstrated that the military policeman who is prepared, updated, and has first aid notions at the moment of emergency care will increase the chances of survival of the victim and highlights the duty of the State in training and maintaining continued education programs directed towards this professional.